Effect of haemodynamic and metabolic predictors on echocardiographic left ventricular mass in non-diabetic hypertensive patients - Gupta, N; Karki, P; Sharma, S; Shrestha, N; Acharya, P (Kathmandu University Medical Journal, 2010)
Background: Left ventricular hypertrophy is a forerunner of coronary heart disease, congestive cardiac failure, stroke and may also lead to sudden death. Estimation of left ventricular mass by echocardiography offers prognostic information better than the evaluation of traditional cardiovascular risk factors. Objective: The aim of this study was to determine the relative contributions of haemodynamic and metabolic factors affecting left ventricular mass in non-diabetic patients with essential hypertension. Material and methods: 100 non-diabetic hypertensive patients were taken. The association between age, gender, smoking, alcohol, height, weight, heart rate, clinic blood pressure, fasting blood glucose, lipid profile, haemoglobin, body mass index and stroke volume with LV mass was studied. Left ventricular mass was measured by using standard M-mode echocardiography measurement obtained by way of standard recommended by the American Society of Echocardiography. Results: Left ventricular mass was analyzed as a continuous variable. In males body mass index (r=.35, p